Aminoglycoside in advanced renal failure - Athukorale, S.D.; Sheriff, M.H.R. (My University, 1984)
Ten patients in advanced renal failure with clinical evidence of septicaemia and positive bacteria isolates from peritoneal dialysate were treated with gentamicin as the aminoglycoside of choice. Two of these patients had to be given netilmicin when gentamicin resistance was obseryed. One patient was placed on tobramycin when she had a gentamicin resistant Pseudomonas aeruginosa isolated from the dialysate. Eight patients responded to therapy with clinical recovery. Nephrotoxicity was not observed. Appropriately chosen aminoglycosides, when carefully monitored, are effective and safe in patients with severely impaired renal function.